Loop flow section conditions of the mixable feed in tilted single-screw batch mixer - Victor F. Khlystunov; Sergey V. Braginets; Mikhail V. Chernutskiy; Anna N. Tokareva (Advanced Engineering Research, 2016)
A mathematical model of the feed mixing in a tilted single-screw circulating batch mixer is presented. The model includes a system of equations of control component concentration change in the representative zones of the mixer. The feed material state at the mixer loading start-up and hulling onset is considered for solving a system of equations. A flow pattern and mathematical expressions of the forces affecting the feed during the charging process are given. As a consequence of the equations solution, the dependence for determining the height of the feed layer on the mixer hopper geometrics and the physical and mechanical-and physical properties of the feed material is obtained. A flow pattern of the forces affecting the feed material at the hulling onset is shown. The layer height value of the hulled material is determined with account of the dependence obtained for the first state of feed. It is determined that two zones are formed from the area of the original conditional displacement. The first one is a plug-flow zone of the bottom-up feed transportation, and the second one is a plug-flow zone in the direction of the downward feed hulling. The cross-sectional area of these zones can be determined on the basis of the derived equations.